The Effect of Workload and Work Ability on the Performance of Family Planning Extension with Employee Well-Being an Intervening Variable in Lamongan Regency - Rafsanjani, Nurdiana; Mujanah, Siti (International Conference On Economics Business Management And Accounting (ICOEMA), 2023)
This study aims to determine the effect of workload and work ability on the performance of Family Planning Extension in Lamongan Regency through employee well-being. The method used is quantitative with 54 respondents from Family Planning Extension in Lamongan Regency and the analysis technique uses SmartPLS 4.0. The test results obtained are: workload has a significant positive effect on employee well-being, work ability has a significant positive effect on employee well-being, employee well-being has a positive significant effect on performance, the workload has no significant effect on performance and work ability has a positive significant effect on performance. The practical implication of this research is that it is hoped that the human resource manager at the Family Planning Extension Instructor in Lamongan Regency pays attention to the ability of employees by providing lots of training to improve employee competence in achieving the set targets.